Epigenetic and metabolic reprogramming of SDH-deficient paragangliomas. Issue 12 (December 2020) - Moog, Sophie; Lussey-Lepoutre, Charlotte; Favier, Judith
Abstract : Pheochromocytomas and paragangliomas (PPGL) are rare neuroendocrine tumors arising from the adrenal medulla or extra-adrenal paraganglia. Around 40% of all cases are caused by a germline mutation in a susceptibility gene, half of which being found in an SDHx gene ( SDHA, SDHB, SDHC, SDHD or SDHAF2 ). They encode the four subunits and assembly factor of succinate dehydrogenase (SDH), a mitochondrial enzyme involved both in the tricarboxylic acid cycle and electron transport chain. SDHx mutations lead to the accumulation of succinate, which acts as an oncometabolite by inhibiting iron(II) and alpha-ketoglutarate-dependent dioxygenases thereby regulating the cell's hypoxic response and epigenetic processes. Moreover, SDHx mutations induce cell metabolic reprogramming and redox imbalance. Major discoveries in PPGL pathophysiology have been made since the initial discovery of SDHD gene mutations in 2000, improving the understanding of their biology and patient management. It indeed provides new opportunities for diagnostic tools and innovative therapeutic targets in order to improve the prognosis of patients affected by these rare tumors, in particular in the context of metastatic diseases associated with SDHB mutations. This review first describes an overview of the pathophysiology and then focuses on clinical implications of the epigenetic and metabolic reprogramming of SDH-deficient PPGL.